2013
DOI: 10.1007/s13197-013-1038-3
|View full text |Cite
|
Sign up to set email alerts
|

Studies on application of annatto (Bixa orellena L.) dye formulations in dairy products

Abstract: Annatto is often used to add color to dairy products such as butter, cheese, or puddings. In India usage of annatto is restricted to butter and cheese, however there are no tailor made formulations available to obtain standardized colour shades for the products. Hence a study was initiated to develop the appropriate annatto dye formulations and level of application in few dairy products (butter, cheese, paneer, biscuit cream, icing cream). Dye extracted from annatto seeds was used for the preparation of water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 17 publications
0
4
0
3
Order By: Relevance
“…Nowadays, these dyes are largely used as substitutes for synthetic dyes in the food and cosmetic industries (Giuliano et al 2003;Dias et al 2011;Marcolino et al 2011;Mala et al 2015) or as histological plant staining (Akinloye et al 2010). Nowadays, these dyes are largely used as substitutes for synthetic dyes in the food and cosmetic industries (Giuliano et al 2003;Dias et al 2011;Marcolino et al 2011;Mala et al 2015) or as histological plant staining (Akinloye et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, these dyes are largely used as substitutes for synthetic dyes in the food and cosmetic industries (Giuliano et al 2003;Dias et al 2011;Marcolino et al 2011;Mala et al 2015) or as histological plant staining (Akinloye et al 2010). Nowadays, these dyes are largely used as substitutes for synthetic dyes in the food and cosmetic industries (Giuliano et al 2003;Dias et al 2011;Marcolino et al 2011;Mala et al 2015) or as histological plant staining (Akinloye et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Norbixin terbentuk dari dimetil ester bixin dan hasil samping degradasi likopen. (Mala & Satyanarayana, 2015). Ekstraksi dari biji kesumba bisa menghasilkan beragam pigmen mulai dari pigmen berwarna kekuningan hingga pigmen berwana kemerahan dan larut kedalam pelarut organik seperti aseton, natrium hidroksida, kloroform, dll.…”
Section: Karakteristik Fisikokimia Pigmen Anattounclassified
“…To avoid environmental toxicity, there is a strong demand to use natural food colours rather than artificial flavours. Many studies have shown that the use of natural colours derived from plants and animals as food additives is acceptable [81]. Singh et al, [82] used lac dye as a food colourant in the meat product, which not only provides a bright red colour but also slightly increases antibacterial and antibacterial action.…”
Section: Foodmentioning
confidence: 99%